PENGARUH PERSEPSI KEBERMANFAATAN DAN PERSEPSI KEMUDAHAN E-SPT PAJAK PENGHASILAN TERHADAP EFISIENSI PEMROSESAN DATA PERPAJAKAN BAGI WAJIB PAJAK BADAN PADA KANTOR PELAYANAN PAJAK PRATAMA CILEGON - Nadya Yuliastuti; Andi Andi (Sains: Jurnal Manajemen dan Bisnis, 2018)
The purpose of this research is to examine the influence on the effect of perceived usefulness and easy of use of e-SPT income tax toward efficiency taxation data processing for the taxation of corporate taxpayers at KPP Pratama Cilegon.Population of this research is the corporate taxpayer using e-SPT. The sample of this research is the corporate taxpayer using e-SPT. Data were analyzed using  software IBM Statistical Package for Social Science (SPSS) version 20. The method used is quantitative analysis, with multiple linear regression model. The results showed that the perception of e-SPT Tax Income efficiency affects the efficiency of tax data processing for corporate taxpayers at KPP Pratama Cilegon. While partically, the ease of e-SPT income tax perception does not affect the efficiency of tax data processing for corporate taxpayer at KPP Pratama Cilegon.